Talectomy for Equinovarus Deformity in Family Members with Hereditary Motor and Sensory Neuropathy Type I - Hristo Georgiev; Georgi P. Georgiev (Case Reports in Orthopedics)
The treatment of severe rigid neurogenic clubfoot deformities still remains a challenging problem in modern paediatric orthopaedics. In those cases, in spite of being a palliative procedure, talectomy has been advocated for the correction of the deformity thus providing a stable plantigrade foot which allows pain-free walking with standard footwear. Herein, we present the results after talectomy in two patients (brother and sister) affected by a hereditary motor and sensory neuropathy type I, with rigid severe pes equinovarus deformities.